From Resilience to Sustainability: The Mediating Role of Emotional Exhaustion and the Direct Effect of Family Support among Mompreneurs in Makassar - Maghfirah Azis; Rahmat Hidayat (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This study examines the role of entrepreneurial resilience in fostering business sustainability, with a focus on emotional exhaustion as an intervening variable and family support as a contextual element. The research used a quantitative cross-sectional approach, encompassing 300 women entrepreneurs (mompreneurs) in Makassar, Indonesia, who concurrently balance business and familial obligations. Data were examined utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect correlations among the hypothesized variables. The results indicate that resilience markedly improves economic sustainability (β = 0.412, p < 0.001) and concurrently diminishes emotional tiredness (β = -0.385, p < 0.001). Emotional exhaustion adversely affects sustainability (β = -0.297, p < 0.001) and partially elucidates the connection between resilience and sustainability (β = 0.114, p < 0.001). Moreover, familial support enhances firm sustainability (β = 0.338, p < 0.001), underscoring the significance of external assistance in maintaining entrepreneurial performance. The structural model accounts for 56.3% of the variance in company sustainability and 14.8% in emotional exhaustion, indicating moderate to great explanatory efficacy. The findings indicate that sustained business is influenced not only by economic or strategic elements but also by psychological resilience and social support networks. This research enhances the entrepreneurial literature by amalgamating psychological and contextual factors into a cohesive framework, specifically with women-led enterprises in emerging economies.